2011
DOI: 10.1097/prs.0b013e3181fed6fd
|View full text |Cite
|
Sign up to set email alerts
|

The Face as a Sensory Organ

Abstract: This review has illustrated the complexity of sensory pathways of the face and their influence on somatic and visceral responses. In view of the discussed data, during facial transplantation, it is important to consider different mechanisms of restoration of facial sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 68 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…While empirical research on this technique is scarce and can only be found as part of DMBI research, according to writings on ancient Shaolin martial arts (Chan & Sze, 2013) [96], the performance of this task is said to clear the nasal orifice, leading to better breathing and psychological well-being. The therapeutic effects of nasal bridge massage is plausible because mindful attention may be simply elicited when one controls his or her fingers in close contact with the face-a significant sensory organ of the body (Siemionow, Gharb, Rampazzo, 2011) [97]. Another somewhat similar technique involving percussion or tapping using fingers on one's face ("Emotional Freedom Techniques") has generated some interest and discussion in the scholastic space as it too seems to be useful for alleviating stress despite its simplicity (Church & Feinstein, 2017) [98].…”
Section: Implications For Sport Psychologymentioning
confidence: 99%
“…While empirical research on this technique is scarce and can only be found as part of DMBI research, according to writings on ancient Shaolin martial arts (Chan & Sze, 2013) [96], the performance of this task is said to clear the nasal orifice, leading to better breathing and psychological well-being. The therapeutic effects of nasal bridge massage is plausible because mindful attention may be simply elicited when one controls his or her fingers in close contact with the face-a significant sensory organ of the body (Siemionow, Gharb, Rampazzo, 2011) [97]. Another somewhat similar technique involving percussion or tapping using fingers on one's face ("Emotional Freedom Techniques") has generated some interest and discussion in the scholastic space as it too seems to be useful for alleviating stress despite its simplicity (Church & Feinstein, 2017) [98].…”
Section: Implications For Sport Psychologymentioning
confidence: 99%
“…Reestablishing sensation and motion for speech, swallow, and mimicry through coaptation of the sensory and motor nerves (trigeminal and facial nerves, respectively) remain challenging. Near normal sensory recovery of the early cases has been demonstrated between 3 and 8 months postoperatively by quantitative sensory tests (18). Motor recovery has been slower with limited published objective data on motor recovery; though the first four patients were able to eat, drink, and speak within 7–10 days after transplantation (14).…”
Section: Obstacles Facing Vascularized Composite Tissue Allotransplanmentioning
confidence: 99%
“…In fact, the face is one of the most important parts of the human anatomy; it plays a major role in basic physical functions and emotions such as swallowing, breathing, seeing, hearing, smelling, smiling and kissing, to name only a few [9]. It represents the central organ of communication, usually the first focus of sexual attractiveness, and the means of immediate recognition by others [81].…”
Section: The Important Role Of Face Allotransplantation In Burnsmentioning
confidence: 99%